Biochemical relationship between glucose-6-phosphate dehydrogenase deficiency and covıd-19 and effects of glutathione supplements - OĞUZ, ESMA; CEBECİ, AYBİKE (My University, 2022)
Glucose-6-phosphate dehydrogenase (G6PD) is an enzyme in the pentose phosphate pathway involved in the production of the reduced form of nicotinamide adenine dinucleotide phosphate (NADPH). One of the most common inherited enzyme abnormalities is G6PD deficiency. G6PD enzyme deficiency facilitates human coronavirus infection due to glutathione (GSH) depletion. Depletion of glutathione due to blockage of the pentose phosphate pathway can hardly preserve the oxidative and anti-oxidative balance. GSH protects the body from the harmful effects of oxidative damage from excess reactive oxygen radicals. Levels of GSH, the key antioxidant protector in all tissues, could be critical in quenching the exacerbated inflammation that triggers organ failure in the new coronavirus disease (COVID-19). Since several amino acids intersect with the GSH pathway, changing the concentrations of these amino acids directly or indirectly can alter cellular GSH homeostasis. Supplementation of amino acids and as well as the implementation of diet strategies offer safe and non-invasive strategies for improving GSH status and protect the body from oxidative stress in various diseases and conditions. The purpose of this review is to examine the biochemical relationship between G6PD deficiency and COVID-19 and the effect of GSH on this disease.

Glikoz-6-fosfat dehidrojenaz (G6PD), indirgenmiş nikotinamid adenin dinükleotid fosfat (NADPH) formunun üretiminde yer alan pentoz fosfat yolağındaki enzimdir. G6PD eksikliği, en yaygın kalıtsal enzim anormalliklerinden biridir. G6PD enzim eksikliği, glutatyon tükenmesine bağlı insan koronavirüs enfeksiyonunu kolaylaştırır. Pentoz fosfat yolunun blokajı nedeniyle glutatyonun (GSH) tükenmesi, oksidatif ve antioksidatif dengeyi zorlukla koruyabilir. GSH, vücudu aşırı reaktif oksijen radikallerinden kaynaklanan oksidatif hasarın zararlı etkilerinden korur. Tüm dokulardaki temel antioksidan koruyucu olan GSH seviyeleri, yeni koronavirüs hastalığında (COVID-19) organ yetmezliğini tetikleyen alevlenen inflamasyonu söndürmede kritik olabilir. Birkaç amino asit GSH yolağı ile kesiştiğinden, bu amino asitlerin konsantrasyonlarını doğrudan veya dolaylı olarak değiştirmek hücresel GSH homeostazını değiştirebilir. Amino asitlerin takviyesi ve diyet stratejilerinin uygulanması, çeşitli hastalık ve koşullarda GSH durumunu iyileştirmek ve vücudu oksidatif stresten korumak için güvenli ve invazif olmayan stratejiler sunar. Bu derlemenin amacı, G6PD eksikliği ile COVID-19 arasındaki biyokimyasal ilişkiyi ve GSH’ın bu hastalık üzerindeki etkisini incelemektir.
Keywords: COVID-19; Glutathione; Glucose-6-phosphate dehydrogenase; Glutatyon; Glukoz-6-fosfat dehidrogenaz